2017
DOI: 10.1080/02656736.2017.1406618
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical radiofrequency induced hyperthermia enhances mitomycin C accumulation in tumour tissue

Abstract: Intravesical RF-CHT results in higher tumour MMC concentrations vs. cold MMC instillation which contributes to its superior efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…Healthy urothelial mucosa has been shown to be less permeable than tumor tissue, hence we believe that intravesical chemotherapy with HT may actually result in an even greater increase of MMC absorption in patients with bladder cancer than demonstrated in our study [17]. Our findings deferred from van Valenberg et al, where they found that MMC concentration did not differ between the cold MMC group and radiofrequency induced MMC group in normal urothelial tissue [15]. This could be attributed to the usage of the Synergo system, which utilizes a 915 MHz antenna to heat the chemotherapeutic agent in the bladder, while having the drug solution constantly pumped out of the bladder and re-instilled after being cooled by the device.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Healthy urothelial mucosa has been shown to be less permeable than tumor tissue, hence we believe that intravesical chemotherapy with HT may actually result in an even greater increase of MMC absorption in patients with bladder cancer than demonstrated in our study [17]. Our findings deferred from van Valenberg et al, where they found that MMC concentration did not differ between the cold MMC group and radiofrequency induced MMC group in normal urothelial tissue [15]. This could be attributed to the usage of the Synergo system, which utilizes a 915 MHz antenna to heat the chemotherapeutic agent in the bladder, while having the drug solution constantly pumped out of the bladder and re-instilled after being cooled by the device.…”
Section: Discussioncontrasting
confidence: 56%
“…Hyperthermia therapy has been shown to improve cancer cell sensitivity to therapeutic agents, cause direct cytotoxicity, trigger anti-cancer immune responses and improve drug delivery for various chemotherapeutic agents to the bladder [12,13,15,16]. Multiple clinical trials treating patients with bladder cancer with intravesical chemotherapy and HT have shown promising results in both the adjuvant setting as well as neoadjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…The two different technologies used in our study in combination with the bladder anatomy may explain the observed differences in heating capacity. Ultimately, the goal of hyperthermia is to have a higher treatment efficacy through an increased drug tumor tissue penetration [28]. Therefore, it would be interesting to compare the resulting efficacy of both RF-HT and C-HT in a clinical setting and correlate it to the achieved tissue-drug concentrations and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HT can potentiate the effect of DOX due to increased tissue penetration and induction of an immune response. 31,32 Administration of DPPG 2 -TSL-DOX was combined with bladder HT to investigate whether this results in higher and more homogeneous distributed DOX concentration in the bladder wall, while limiting DOX concentration in essential organs, compared to conventional DOX application (ie, iv administration, intravesical instillation and CHT). Since the physiology and urinary tract anatomy of pigs closely resembles that of humans, a pig bladder model was used.…”
Section: Introductionmentioning
confidence: 99%